Health advocacy training in urology: a Canadian survey on - Leveridge, Michael; Beiko, Darren; Wilson, James W.L.; Siemens, Robert (Canadian Urological Association Journal, 2013)
Introduction: Health advocacy is a well-defined core competency recognized by medical education and regulatory bodies. Advocacy is stressed as a critical component of a physician’s function within his or her community and also of performance evaluation during residency training. We sought to assess urology residents’ perceptions and attitudes toward health advocacy in residency training and practice. Methods: We administered an anonymous, cross-sectional, self-report questionnaire to all final-year urology residents in Canadian training programs. The survey was closed-ended and employed a 5-point Likert scale. It was designed to assess familiarity with the concept of health advocacy and with its application and importance to training and practice. We used descriptive and correlative statistics to analyze the responses, such as the availability of formal training and resident participation in activities involving health advocacy. Results: There was a 93% response rate among the chief residents. Most residents were well aware of the role of the health advocate in urology, and a majority (68%) believed it is important in residency training and in the urologist’s role in practice. This is in stark contrast to acknowledged participation and formal training in health advocacy. A minority (7%–25%) agreed that formal training or mentorship in health advocacy was available at their institution, and only 21%–39% felt that they had used its principles in the clinic or community. Only 4%–7% of residents surveyed were aware of or had participated in local urological health advocacy groups. Conclusion: Despite knowledge about and acceptance of the importance of the health advocate role, there is a perceived lack of formal training and a dearth of participation during urological residency training.